Blockchain Based Decentralized User Identity Verification System - Subham Gangurde, Sudarshan Gawale, Harshal Walunj, Gauri Shivsharan, Kavita A. Sultanpure (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Privacy is a fundamental consumer right, and the data provided by users is handled by only a few of the large centralized entities that control the majority of the internet. Thus, transferring this data to a decentralized entity such as a blockchain would be an excellent solution. Blockchain stores data in a decentralized and highly secure manner, ensuring data security and integrity. Users will also have authority and control over their data which provides a more effective solution to the current problem. As a result, user authentication via blockchain could be a significant fundamental building block for the next generation of the web (Web 3.0).